Striatal dopamine transporter imaging correlates with depressive symptoms and tower of London task performance in Parkinson's disease - Rektorova, Irena; Srovnalova, Hana; Kubikova, Radka; Prasek, Jiri (Movement disorders, 2008)
We studied whether the (123)I-FP-CIT uptake in the striatum correlates with depressive symptoms and cognitive performance in patients with Parkinson's disease (PD). Twenty patients with PD without major depression and/or dementia (mean age 61.7 +/- 12.7 years) underwent the (123)I-FP-CIT SPECT. Depressive symptoms and cognitive performance were assessed in the ON state. The ratios of striatal to occipital binding for the entire striatum, putamina, and putamen to the caudate (put/caud) index were calculated in the basal ganglia. The association between neuropsychiatric measures and dopamine transporter (DAT) availability was calculated; multiple regression analysis was used to assess association with age and disease duration. We found significant correlations between Montgomery and Asberg Depression Rating Scale (MARDS) and Tower of London (TOL) task scores and (123)I-FP-CIT uptake in various striatal ROIs. Multiple regression analysis confirmed the significant relationship between TOL performance and put/caud ratio (P = 0.001) and to age (P = 0.001), and between MADRS and left striatal (P = 0.005) and putaminal DAT availability (P = 0.003). Our pilot study results demonstrate that imaging with (123)I-FP-CIT SPECT appears to be sensitive for detecting dopaminergic deficit associated with mild depressive symptoms and specific cognitive dysfunction in patients with PD, yet without a current depressive episode and/or dementia.
Keywords: Regression Analysis; Female; Parkinsonova nemoc; Neuropsychological Tests; ženské pohlaví; corpus striatum; tropany; Corpus Striatum; neuropsychologické testy; lidé; regresní analýza; stupeň závažnosti nemoci; Tropanes; kognice; Dopamine Plasma Membrane Transport Proteins; Tomography, Emission-Computed, Single-Photon; Male; Aged; Cognition; proteiny přenášející dopamin přes plazmatickou membránu; lidé středního věku; deprese; senioři; mužské pohlaví; Severity of Illness Index; Depression; Iodine Radioisotopes; Middle Aged; jednofotonová emisní výpočetní tomografie; radioizotopy jodu; Parkinson Disease; Humans